Bridging Skills and Language: Developing Web-Based English Learning Platforms for Vocational Education - Ahmad Rossydi; Peter John Wanner; Muawal Al As’ary; Benny Kurnianto; Aat Eska Fahmadi (Universitas Negeri Makassar, 2026)
This research is based on the rapid development of Information and Communication Technology (ICT) in the education sector. Developing a web-based English learning platform tailored to vocational students not only meets the demand for innovative educational solutions but also improves their language competence and prepares them for the job market. It also promotes access, scalability, 21st-century skills, and real-life issues, and helps shape what a modern, accessible, 21st-century education is like. This study aims to contribute to addressing the increasingly widespread demand for ICT integration in education, especially in vocational higher education, and to reconcile technology with human resource development. The study's objective was to develop a web-based learning platform,